2022
DOI: 10.14710/ijred.2022.45306
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of a Solar PV/T Air Collector Under the Climatic Conditions of Zarqa, Jordan

Abstract: The use of hybrid photovoltaic/thermal (PV/T) and low concentrating photovoltaic/thermal (LCPV/T) systems can significantly enhance the overall solar energy conversion efficiency by delivering electricity and thermal energy. This paper presents a case study using a standing PV system's theoretical and modeling approach that can be modified to adapt to the hybrid technology. Firstly, a single-pass conventional PV/T air-cooled collector is investigated based on heat transfer and electrical models under the clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…As a result, additional thermal energy was received by the flowing water, and thermal efficiency was increased from 24% to 58%. Nijmeh et al (Nijmeh et al, 2022) observed a slight improvement in electrical efficiency in a PV/T compared to a PV module. The efficiency was further improved with the application of a solar concentrator to the PV/T system.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, additional thermal energy was received by the flowing water, and thermal efficiency was increased from 24% to 58%. Nijmeh et al (Nijmeh et al, 2022) observed a slight improvement in electrical efficiency in a PV/T compared to a PV module. The efficiency was further improved with the application of a solar concentrator to the PV/T system.…”
Section: Introductionmentioning
confidence: 99%